2021
DOI: 10.1002/osp4.562
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ perspectives on perceived usefulness of digital and in‐person diabetes prevention programs: A qualitative study to inform decisions related to program participation

Abstract: Objective: Given the effectiveness of both in-person and digital diabetes prevention programs (DPPs), participants have an opportunity to select a delivery mode based on their needs and preferences. The objective of this study was to understand and compare participants' experiences with digital and in-person DPPs to identify factors that affected how useful participants perceived these two program delivery modes. Methods: Semi-structured interviews with participants who were enrolled in DPPs as either a digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…This is comparable to a recent large study from the Diabetes Prevention Research Group that analyzed 41,000 members of in‐person DPPs and observed a median retention of 28 weeks (IQR 15, 41) 34 . However, comparing in‐person and digital DPPs may not be of high importance given that both are recognized by the CDC 36 and perceived by participants to be similarly useful and beneficial for different reasons 37 . Having different modes of delivery enables participating members to select a program that best meets their individual needs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is comparable to a recent large study from the Diabetes Prevention Research Group that analyzed 41,000 members of in‐person DPPs and observed a median retention of 28 weeks (IQR 15, 41) 34 . However, comparing in‐person and digital DPPs may not be of high importance given that both are recognized by the CDC 36 and perceived by participants to be similarly useful and beneficial for different reasons 37 . Having different modes of delivery enables participating members to select a program that best meets their individual needs.…”
Section: Discussionsupporting
confidence: 77%
“… 34 However, comparing in‐person and digital DPPs may not be of high importance given that both are recognized by the CDC 36 and perceived by participants to be similarly useful and beneficial for different reasons. 37 Having different modes of delivery enables participating members to select a program that best meets their individual needs. The program that offers the best fit for a particular member should be the one that encourages the longest retention and thus facilitates the best outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Development and use of digital and online platforms to deliver DPP has increased considerably over the years 21 . In addition to its proven effectiveness for weight loss, 22–25 digital DPP has a broader reach than in‐person and is considered more convenient by participants 26 . Given that digital DPP has the potential to expand access to an evidence‐based behavioral intervention, which has become even more imperative during the COVID‐19 pandemic, it seems relevant to also examine the effectiveness of this delivery modality in the context of mental health.…”
Section: Introductionmentioning
confidence: 99%
“… 21 In addition to its proven effectiveness for weight loss, 22 , 23 , 24 , 25 digital DPP has a broader reach than in‐person and is considered more convenient by participants. 26 Given that digital DPP has the potential to expand access to an evidence‐based behavioral intervention, which has become even more imperative during the COVID‐19 pandemic, it seems relevant to also examine the effectiveness of this delivery modality in the context of mental health. Therefore, this study examined the moderating effect of a mental health diagnosis on weight change over a 12 and 24‐month period among older adults who were invited to participate in digital DPP.…”
Section: Introductionmentioning
confidence: 99%